O płynności teorii naukowej. Na marginesie książki Andrzeja Klawitera „Postawa badawcza i struktura wyboru teoretycznego” - Nowak, Leszek (Filozofia Nauki, 1993)
The author, starting from the critical review of Andrzej Klawiter's book (in Polish) „Research attitude and the structure of theoretical choice”, comes to consider questions concerning the opposition act/product in science and the problem of scientific interpretation. The considerations give him an occasion to formulate some rules of canonical scientific text formation (i.e. rules of cognitivism, clarity, contradiction, logical consistency, completness and consistency of interpretation).